Analysis of the expression of transcripts at imprinted loci across mammalian species during early development - Ramirez, Sylvia (Jihočeská univerzita, 2019)
To explore the conservation of novel transcripts in imprinted regions identified in mouse and developmental regulation of transcripts in imprinted loci, RNA-seq datasets from six mammalian species from various developmental stages were processed followed by de novo transcriptome assembly, filtering and downstream analysis.
Analysis of the expression of transcripts at imprinted loci across mammalian species during early development